Endoscopic stapedotomy: Merits and demerits - Waleed Moneir; Ahmed Musaad Abd El-fattah; Eslam Mahmoud; Mohamed Elshaer (Journal of Otology)
A one-year-old baby girl with one-month history of recurrent pus fluid exuding from her left preauricular sinus orifice, who failed multiple courses of surgical drainage of the abscess and persistent debridement for the wound, presented with MRSA infection. The patient was treated with linezolid for three days. Her pain and paresthesia resolved, and C-reactive protein decreased to normal.